Management Information System for Human Resources at the Operational Bureau of the DIY Regional Police using Agile Development Method - Saputro, Bayu; Rianto, Rianto; Wahana, Aditya (LPPM UTDI (d.h STMIK AKAKOM) Yogyakarta, 2024)
This research develops Agile Development, particularly Extreme Programming (XP), to create a web-based Human Resource Management Information System for the DIY Regional Police's Operational Bureau. Addressing challenges in personnel data management, the objective is to enhance efficiency and effectiveness. The study involves system needs analysis, design, implementation, and testing. Initial development includes interfaces for employees, administrators, and leaders, featuring personnel data management, leave requests, and announcements. Testing involves White Box, Black Box, and alpha testing by 25 Operational Bureau respondents. Alpha test results reveal high satisfaction with efficiency, data accuracy, and administrative process acceleration. The system effectively reduces human errors in personnel data management. The research concludes that the web-based system is a successful, computerized, organized solution for personnel data management in the Operational Bureau of DIY Regional Police